2019
DOI: 10.3748/wjg.v25.i47.6813
|View full text |Cite
|
Sign up to set email alerts
|

Non-SMC condensin I complex subunit D2 and non-SMC condensin II complex subunit D3 induces inflammation via the IKK/NF-κB pathway in ulcerative colitis

Abstract: BACKGROUNDUlcerative colitis (UC) is a chronic, nonspecific intestinal inflammatory disease with undefined pathogenesis. Non-SMC condensin I complex subunit D2 (NCAPD2) and non-SMC condensin II complex subunit D3 (NCAPD3) play pivotal roles in chromosome assembly and segregation during both mitosis and meiosis. To date, there has been no relevant report about the functional role of NCAPD2 and NCAPD3 in UC.AIMTo determine the level of NCAPD2/3 in intestinal mucosa and explore the mechanisms of NCAPD2/3 in UC.ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In detail, patient SN3 has the variant c.1712A>C; p.His571Pro within the NCAPD3 gene, while subject SN5 carries the variant c.860C>G; p.Pro287Arg within NCAPD2 . Both genes have a role in releasing pro-inflammatory cytokine and modulating the NF-κB signalling pathway [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In detail, patient SN3 has the variant c.1712A>C; p.His571Pro within the NCAPD3 gene, while subject SN5 carries the variant c.860C>G; p.Pro287Arg within NCAPD2 . Both genes have a role in releasing pro-inflammatory cytokine and modulating the NF-κB signalling pathway [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…After stimulation, I κ B kinase (IKK) becomes phosphorylated, resulting in the phosphorylation of I κ B, which dissociates from NF- κ B and enters the nucleus to regulate the secretion and expression of inflammatory factors. The activation of IKK/NF- κ B, which is an essential cause of severe inflammation [ 35 , 36 ], increases the secretion of the proinflammatory cytokines and induces inflammatory reactions [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gan et al [ 27 ] reported that KIF2C is a target gene of miR-325-3p, which has been shown to be a tumor suppressor in non-small-cell lung cancer. Yuan et al [ 28 ] reported that over-expression of NCAPD2/3 promotes the release of pro-inflammatory cytokines by modulating the IKK/NF-κB signaling pathway. Han et al [ 29 ] reported that TRAIP is crucial in early mitotic progression and chromosome alignment defects in the metaphase.…”
Section: Discussionmentioning
confidence: 99%